2020
DOI: 10.1111/jgh.15039
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of esophageal adenocarcinoma metastasis via Wnt/ß‐catenin signal pathway by sorting nexins 3

Abstract: Background: Esophageal adenocarcinoma is often associated with late diagnoses, poor prognoses, significant morbidities, and high mortality rates. Aberrant expression of Wnt/β-catenin signal pathways were observed in the tumorigenesis and metastasis of esophageal adenocarcinoma. Sorting nexins 3 has been shown to participate in Wnt protein sorting and regulate Wnt/β-catenin signal transduction. Thus, we studied the role and molecular mechanism of sorting nexins 3 in esophageal adenocarcinoma. Methods: Tissue mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Another study including 9,934 stage I–IV patients with EC suggested that the AC subtype was more likely to cause BM than SCC tumors ( 7 ). The exact mechanism for this metastasis remains unclear, several researchers have pointed out that high expression of sorting nexin 3, sphingosine-1-phosphate receptor 2, and toll-like receptor 9 may explain the high invasiveness of AC in patients with EC ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study including 9,934 stage I–IV patients with EC suggested that the AC subtype was more likely to cause BM than SCC tumors ( 7 ). The exact mechanism for this metastasis remains unclear, several researchers have pointed out that high expression of sorting nexin 3, sphingosine-1-phosphate receptor 2, and toll-like receptor 9 may explain the high invasiveness of AC in patients with EC ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%